Histamine Increases Neuronal Excitability and Sensitivity of the Lateral Vestibular Nucleus and Promotes Motor Behaviors via HCN Channel Coupled to H2 Receptor - Li, Bin; Zhang, Xiao-Yang; Yang, Ai-Hong; Peng, Xiao-Chun; Chen, Zhang-Peng; Zhou, Jia-Yuan; Chan, Ying-Shing; Wang, Jian-Jun; Zhu, Jing-Ning (Frontiers in Cellular Neuroscience, 2017)
Histamine and histamine receptors in the central nervous system actively participate in modulation of motor control. In clinic, histamine-related agents have traditionally been used to treat vestibular disorders. Immunohistochemical studies have revealed a distribution of histaminergic afferents in the brainstem vestibular nuclei, including the lateral vestibular nucleus (LVN), which is critical for adjustment of muscle tone and vestibular reflexes. However, the mechanisms underlying the effect of histamine on LVN neurons and the role of histamine and histaminergic afferents in the LVN in motor control are still largely unknown. Here, we show that histamine, in cellular and molecular levels, elicits the LVN neurons of rats an excitatory response, which is co-mediated by the hyperpolarization-activated cyclic nucleotide-gated (HCN) channels and K+ channels linked to H2 receptors. Blockage of HCN channels coupled to H2 receptors decreases LVN neuronal sensitivity and changes their dynamic properties. Furthermore, in behavioral level, microinjection of histamine into bilateral LVNs significantly promotes motor performances of rats on both accelerating rota-rod and balance beam. This promotion is mimicked by selective H2 receptor agonist dimaprit, and blocked by selective H2 receptor antagonist ranitidine. More importantly, blockage of HCN channels to suppress endogenous histaminergic inputs in the LVN considerably attenuates motor balance and coordination, indicating a promotion role of hypothalamo-vestibular histaminergic circuit in motor control. All these results demonstrate that histamine H2 receptors and their coupled HCN channels mediate the histamine-induced increase in excitability and sensitivity of LVN neurons and contribute to the histaminergic improvement of the LVN-related motor behaviors. The findings suggest that histamine and the histaminergic afferents may directly modulate LVN neurons and play a critical role in the central vestibular-mediated motor reflexes and behaviors.